Xanthine oxidase inhibitors are associated with reduced risk of cardiovascular disease - Saito, Hirotaka (Sci Rep, 2021)
As previous studies have reported finding an association between hyperuricemia and the development of cardiovascular and chronic kidney disease, hyperuricemia is thought to be an independent risk factor for hypertension and diabetic mellitus. However, we have not been able to determine whether the use of xanthine oxidase inhibitors can reduce cardiovascular disease. The present study used the longitudinal data of the Fukushima Cohort Study to investigate the relationship between the use of xanthine oxidase inhibitors and cardiovascular events in patients with cardiovascular risks. During the 3-year period between 2012 and 2014, a total of 2724 subjects were enrolled in the study and followed. A total of 2501 subjects had hypertension, diabetic mellitus, dyslipidemia, or chronic kidney disease, and were identified as having cardiovascular risks. The effects of xanthine oxidase inhibitor use on the development of cardiovascular events was evaluated in these patients using a time to event analysis. During the observational periods (median 2.7 years), the incidence of cardiovascular events was 20.7 in subjects with xanthine oxidase inhibitor and 11.2 (/1000 person-years, respectively) in those without. Although a univariate Cox regression analysis showed that the risk of cardiovascular events was significantly higher in subjects administered xanthine oxidase inhibitors (HR = 1.87, 95% CI 1.19–2.94, p = 0.007), the risk was significantly lower in subjects administered a xanthine oxidase inhibitor after adjustment for covariates (HR = 0.48, 95% CI 0.26–0.91; p = 0.024) compared to those without. Xanthine oxidase inhibitor use was associated with reduced risk of cardiovascular disease in patients with cardiovascular risk factors.